Structure-activity relationships of nucleoside analogues for inhibition of tick-borne encephalitis virus - Eyer, Luděk; Šmídková, Markéta; Nencka, Radim; Neča, Jiří; Kastl, Tomáš; Palus, Martin; De Clercq, Erik; Růžek, Daniel (Antiviral research, 2016)
Tick-borne encephalitis (TBE) represents one of the most serious arboviral neuro-infections in Europe and northern Asia. As no specific antiviral therapy is available at present, there is an urgent need for efficient drugs to treat patients with TBE virus (TBEV) infection. Using two standardised in vitro assay systems, we evaluated a series of 29 nucleoside derivatives for their ability to inhibit TBEV replication in cell lines of neuronal as well as extraneural origin. The series of tested compounds included 2'-C- or 2'-O-methyl substituted nucleosides, 2'-C-fluoro-2'-C-methyl substituted nucleosides, 3'-O-methyl substituted nucleosides, 3'-deoxynucleosides, derivatives with 4'-C-azido substitution, heterobase modified nucleosides and neplanocins. Our data demonstrate a relatively stringent structure-activity relationship for modifications at the 2', 3', and 4' nucleoside positions. Whereas nucleoside derivatives with the methylation at the C2' position or azido modification at the C4'position exerted a strong TBEV inhibition activity (EC50 from 0.3 to 11.1 μM) and low cytotoxicity in vitro, substitutions of the O2' and O3' positions led to a complete loss of anti-TBEV activity (EC50 > 50 μM). Moreover, some structural modifications of the heterobase moiety resulted in a high increase of cytotoxicity in vitro. High antiviral activity and low cytotoxicity of C2' methylated or C4' azido substituted pharmacophores suggest that such compounds might represent promising candidates for further development of potential therapeutic agents in treating TBEV infection.
Keywords: Animals; Antiviral Agents; Nucleoside inhibitor; vztah mezi dávkou a účinkem léčiva; buněčné linie; Structure-activity relationship; antivirové látky; Molecular Structure; Nucleosides; Structure-Activity Relationship; replikace viru; prasata; viry klíšťové encefalitidy; nukleosidy; Tick-borne encephalitis; Cell Line; Encephalitis Viruses, Tick-Borne; molekulární struktura; Dose-Response Relationship, Drug; Swine; Encephalitis, Tick-Borne; vztahy mezi strukturou a aktivitou; Antiviral activity; zvířata; klíšťová encefalitida; Virus Replication; Cytotoxicity